Quality improvement mechanism for cyber physical systems—An evaluation. Issue 11 (19th June 2020) - Regan, Gilbert; McCaffery, Fergal; Paul, Pangkaj Chandra; Reich, Jan; Armengaud, Eric; Kaypmaz, Cem; Zeller, Marc; Guo, Joe Zhensheng; Longo, Simone; O'Carroll, Eoin; Sorokos, Ioannis
Abstract: The future will encompass heavily interconnected, distributed, heterogeneous and intelligent systems which are bound to have a significant economic and social impact. Cyber physical systems (CPS) such as autonomous cars, smart electric grid, implanted medical devices and smart manufacturing are some practical examples of these intelligent systems. However, due to the open and cooperative nature of CPS, assuring their dependability is a challenge. The DEIS project addresses this important and unsolved challenge by developing the concept of a digital dependability identity (DDI). A DDI contains all the information that uniquely describes the dependability characteristics of a CPS or CPS component. DDIs are synthesised at development time and are the basis for the (semi)automated integration of components into systems during development, as well as for the fully automated dynamic integration of systems into systems of systems in the field. Abstract : In this paper, we present an overview of the DDI. We provide the metric selection process for evaluating the DDI's impact on CPS dependability. The results of an evaluation of the DDI's impact on dependability in four CPS industrial systems are provided, both for design time and runtime. These results demonstrate the positive impact of the DDI on the dependability of CPS.